令x1=x2=0,則f(0+0)=f(0)+f(0)-1?f(0)=1,
令x1=x,x2=-x,則f(x-x)=f(x)+f(-x)-1,
∴[f(x)-1]+[f(-x)-1]=0,
∴f(x)-1為奇函數(shù).
(2)由(1)知,f(x)-1為奇函數(shù),
∴f(-x)-1=-[f(x)-1],
任取x1,x2∈R,且x1<x2,則x2-x1>0,
∵f(x1+x2)=f(x1)+f(x2)-1,
∴f(x2-x1)=f(x2)+f(-x1)-1=f(x2)-[f(x1)-1]=
f(x2)-f(x1)+1.
∵當x>0時,f(x)>1,
∴f(x2-x1)=f(x2)-f(x1)+1>1,∴f(x1)<f(x2),
∴f(x)是R上的增函數(shù).
(3)∵f(x1+x2)=f(x1)+f(x2)-1,且f(4)=5,
∴f(4)=f(2)+f(2)-1?f(2)=3.
由不等式f(3m2-m-2)<3,得f(3m2-m-2)<f(2),
由(2)知,f(x)是R上的增函數(shù),
∴3m2-m-2<2,∴3m2-m-4<0,∴-1<m<
4 |
3 |
∴不等式f(3m2-m-2)<3的解集為(-1,
4 |
3 |